Предмет: Алгебра,
автор: dianavasileva2007
(x+1)(x^2-x+1)(x^6-x^3+1)=
СРОЧНО, ПРОШУ, ЭТО НЕ НАДО СДАТЬ УЖЕ ЗАВТРА!!!
Ответы
Автор ответа:
1
Ответ:
Объяснение: (а+в)(а²-ав+в²)=(а³+в³)
два раза используем одну и ту же формулу суммы кубов.
(x+1)(x^2-x+1)=(х³+1)
(х³+1)(x⁶-x³+1)=(х⁹+1)
(x+1)(x^2-x+1)(x^6-x^3+1)=(х⁹+1)
Похожие вопросы
Предмет: Математика,
автор: mitya7
Предмет: Русский язык,
автор: ubabina
Предмет: Алгебра,
автор: 123qween123
Предмет: Литература,
автор: nik292445
Предмет: Биология,
автор: Ира2100